2017
DOI: 10.1590/1807-3107bor-2017.vol31.0063
|View full text |Cite
|
Sign up to set email alerts
|

Different engagement of TLR2 and TLR4 in Porphyromonas gingivalis vs. ligature-induced periodontal bone loss

Abstract: This study was conducted to investigate the roles of different Toll-like receptor (TLR) signaling in Porphyromonas gingivalis (P. gingivalis)-induced and ligature-induced experimental periodontal bone resorption in mice. Wild-type (WT), TLR2 knockout (KO), TLR4KO, and TLR2&4 KO mice with C57/BL6 background were divided into three groups: control, P. gingivalis infection, and ligation. Live P. gingivalis or silk ligatures were placed in the sulcus around maxillary second molars over a 2-week period. Images were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 30 publications
2
24
0
4
Order By: Relevance
“…5B) observed in WT mice were diminished in TLR4 KO mice. The differences in pathogenesis and disease progression between peri‐implantitis and periodontitis may be a reason why the RANKL/OPG ratio was significantly changed between the control group and the P. gingivalis‐ Lig group in the TLR4 KO mice in experimental periodontitis but not in experimental peri‐implantitis (Fig. 3E).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5B) observed in WT mice were diminished in TLR4 KO mice. The differences in pathogenesis and disease progression between peri‐implantitis and periodontitis may be a reason why the RANKL/OPG ratio was significantly changed between the control group and the P. gingivalis‐ Lig group in the TLR4 KO mice in experimental periodontitis but not in experimental peri‐implantitis (Fig. 3E).…”
Section: Discussionmentioning
confidence: 99%
“…Our previously studies indicated that TLR4 could recognize the surface components of P. gingivalis and promote the proinflammatory cytokine responses and osteoclastogenesis in P. gingivalis associated ligature induced periodontitis . Moreover, P. gingivalis ‐induced periodontal bone resorption is TLR4‐dependent . The purpose of this study is to determine the role of TLR4 signaling in peri‐implantitis inflammation and bone loss and its associated cellular and molecular mechanism, using a mouse model of P. gingivalis ‐associated ligature induced experimental peri‐implantitis.…”
Section: Introductionmentioning
confidence: 98%
“…TRAP-positive cells (red color) with 3 or more nuclei were considered osteoclasts and were shown in the control group, ligation group, ligation with anti-RANKL antibody treatment group, and ligation with anti-RANKL antibody + miR-146a treatment group in WT mice and TLR2/4 KO mice (a) (Im, implant; Av, alveolar bone; scale bar, 100 μm). The quantities of TRAP-positive cells were analyzed in each group of WT mice (b) and TLR2/4 KO mice (c) (mean ± SD, n = 6, **p < 0.01) are essential signaling proteins in progression of inflammation and related bone metabolism in periodontitis [28,29,39,40]. However, little is known about the functions of TLR2 and TLR4 signaling in peri-implantitis.…”
Section: Discussionmentioning
confidence: 99%
“…Toll-like receptors (TLR) are a family of wellcharacterized pattern recognition receptors (PRRs) and play an important role in the induction of pro-inflammatory cytokines by recognizing the signature molecules of the host innate immunity [25][26][27]. Our previous studies showed that TLR2 are associated with implant bone loss in a mouse model of peri-implantitis [5] and TLR4 is essential for periodontal bone loss [28,29]. In our previous study, we examined the changes of inflammatory cytokines and bone metabolism cytokines in either TLR2 only KO mice or TLR4 only KO mice [5,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation